2021
DOI: 10.1007/s40620-021-01130-x
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of risk factors and outcomes of neonatal acute kidney injury

Abstract: Introduction Neonatal Acute kidney injury (AKI) is an underestimated morbidity in the neonatal intensive care unit (ICU). However, there is a paucity of information about risk factors, outcomes, and possible preventive measures to limit its occurrence. Aim This study aimed to determine the prevalence of neonatal AKI in a neonatal ICU. Data obtained from this study will help to better understand current local practices and investigate possible preventive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 22 publications
2
17
0
2
Order By: Relevance
“…Elmas et al [25] have observed a significant incidence of AKI in neonates having a central venous catheter (p 0.001) and umbilical catheter (p 0.002). AlGadeeb has documented that the presence of central lines, as well as umbilical arterial catheter, are significantly associated with AKI [27]. In our cohort, all neonates with central lines had a significantly higher incidence of AKI.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Elmas et al [25] have observed a significant incidence of AKI in neonates having a central venous catheter (p 0.001) and umbilical catheter (p 0.002). AlGadeeb has documented that the presence of central lines, as well as umbilical arterial catheter, are significantly associated with AKI [27]. In our cohort, all neonates with central lines had a significantly higher incidence of AKI.…”
Section: Discussionmentioning
confidence: 52%
“…Jetton et al analysis shows that neonates with AKI have 8.8 times longer duration of stay and 4.6 times higher mortality as compared to the non-AKI group [5]. Comparing different stages of AKI, the higher the order of renal failure poor is the outcome [11,20,21,26,27]. Irrespective of severity, all neonates in our cohort with AKI had significantly longer length of stay and higher odds of death.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations